Footprints in Aggieland : Remembrances of a Veteran Fundraiser - Walker, Robert L., 1936- (Book collections on Project MUSE., 2015)
ROBERT L. WALKER has served for more than five critical decades in leading fundraising roles at Texas A & M University, including holder of the distinctive James Aston University Chair in Institutional Development. Recently retired from Texas A & M, he still lives in College Station, where he and his son, Sid A. Walker, manage The Walker Consulting Group.